IMPROVING ASEAN AND ITS MEMBER COUNTRIES ROLE IN MIGRANT WORKERS PROTECTION IN ASEAN COMMUNITY - Setiawan Wicaksono (University of Sumatera Utara, 2017)
The goals of this article which based on a research are to find out the obstacles in migrant workers protection, which initially had already been agreed in ASEAN Social Culture Community (ASCC), and how ASEAN and its members’ effort to actively protect migrant workers based on ASCC in ASEAN Community. Research method used in this article is normative legal studies. The results are ASCC Blueprint still general in its formulation and resulting problems when applied into national law, regulation institutionalisation was not at ease due to the long procedure which augmented with sovereignity issue that gives states the rights to determine its internal interest. ASEAN as regional organization must able to maximise the role of mechanism and organs in its possession to push the regulation into national law of its member states in order to ensure institusionalisation. The member states also have to own a concept on how regionalism is, and willing to relegate souveregnity so ASCC Blueprint and its derived instrumens can easily be fused into national law and work well.